2016
DOI: 10.1097/ta.0000000000001190
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the protein C pathway and endothelial glycocalyx shedding is associated with coagulopathy in an ovine model of trauma and hemorrhage

Abstract: Animals in the severe trauma group developed coagulation changes consistent with current definitions of ATC. The degree of coagulopathy was correlated with the degree of shock, quantified by arterial lactate. Activation of the protein C pathway and endothelial glycocalyx shedding were correlated with the development of coagulopathy; however, altered platelet function was not evident in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…This finding indicates that catecholamine release activates the inflammatory response in trauma and induction of TNF‐α may be the mechanism for EG loss as previously hypothesized 157 . In experimental animal shock models and clinical human trials, a large catecholamine surge and tissue hypoperfusion that occur in shock appear to be associated with widespread loss of the EG 129,155 . Massive EG loss in trauma is associated with increased vascular permeability, increased systemic inflammation, hypocoagulability, and reduced vascular responsivess 116,129,130 …”
Section: Disease States Leading To Glycocalyx Dysfunctionsupporting
confidence: 59%
See 4 more Smart Citations
“…This finding indicates that catecholamine release activates the inflammatory response in trauma and induction of TNF‐α may be the mechanism for EG loss as previously hypothesized 157 . In experimental animal shock models and clinical human trials, a large catecholamine surge and tissue hypoperfusion that occur in shock appear to be associated with widespread loss of the EG 129,155 . Massive EG loss in trauma is associated with increased vascular permeability, increased systemic inflammation, hypocoagulability, and reduced vascular responsivess 116,129,130 …”
Section: Disease States Leading To Glycocalyx Dysfunctionsupporting
confidence: 59%
“…In people, clinical studies have demonstrated an increase in EG biomarkers, including HS, HA, SDC1, and CS, after trauma or hemorrhagic shock 130,153 . Unfortunately, there are currently no clinical veterinary studies investigating the link between EG degradation and trauma; however, animal hemorrhagic shock models have demonstrated EG loss after serious hemorrhage 154,155 …”
Section: Disease States Leading To Glycocalyx Dysfunctionmentioning
confidence: 99%
See 3 more Smart Citations